2006
DOI: 10.1111/j.1525-1470.2006.00278.x
|View full text |Cite
|
Sign up to set email alerts
|

The Prognostic Value of Nailfold Capillary Changes for the Development of Connective Tissue Disease in Children and Adolescents with Primary Raynaud Phenomenon: A Follow‐up Study of 250 Patients

Abstract: To assess the prognostic value of capillaroscopy findings for the development of connective tissue disease in children and adolescents with Raynaud phenomenon, we followed up a group of 250 (mean age 15 years) for 1 to 6 years after the first capillaroscopy was performed. Every 6 months they were screened for signs and symptoms of connective tissue disease. Analysis was performed on capillary changes registered 6 months before the development of connective tissue disease. Capillary changes were classified into… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0
9

Year Published

2007
2007
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(37 citation statements)
references
References 22 publications
0
28
0
9
Order By: Relevance
“…Those changes are more often found in patients with polyarticular JIA and positive for RF and ANA. 19,20 In our study, those changes were not found, maybe because of the small amount of patients with those antibodies. However, patients with RP show more changes on NFC, indicating that they probably have vasculopathy.…”
Section: Discussionmentioning
confidence: 55%
“…Those changes are more often found in patients with polyarticular JIA and positive for RF and ANA. 19,20 In our study, those changes were not found, maybe because of the small amount of patients with those antibodies. However, patients with RP show more changes on NFC, indicating that they probably have vasculopathy.…”
Section: Discussionmentioning
confidence: 55%
“…The very low risk of developing SSc and other CTD in people presenting with normal capillary pattern has been confi rmed in a recent larger trial [36]. While up to 60 % of healthy persons might exhibit single or combined abnormalities of a scleroderma pattern, megacapillaries and avascular fi elds are not expected in the 'normal population', nor is it expected in primary RP [18,19].…”
Section: Discussion Of the Diagnostic Valuementioning
confidence: 91%
“…The prediction of a typical scleroderma pattern for the identifi cation of actual connective tissue disease or its subsequent development is high, whereas the negative prediction for a normal microscopic pattern is excellent [36,42,49,64].…”
Section: Discussion Of the Diagnostic Valuementioning
confidence: 99%
See 1 more Smart Citation
“…Kız/erkek oranı 1.7'di. Hastaların medyan (minimum-maksimum) semptom başlangıç yaşı 12 (5-16); tanı yaşı 13 (5.5-16); çalışmaya dahil edildikleri andaki yaşları 15 (7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19) Raynaud fenomeninin tedavisi için yapılmış klinik çalışma ve kılavuzlar halen yetersiz olsa da genel görüş soğuk, stres gibi tetikleyici faktörlerden kaçınmanın faydalı olduğu yönündedir (15). Genel önlemlerin başarısız olduğu olgularda ilk basamak tedavi kalsiyum kanal blokörleridir.…”
Section: Bulgularunclassified